LCoS-Based Wavelength-Selective Switch for Future Finer-Grid Elastic Optical Networks Capable of All-Optical Wavelength Conversion - Dequan Xie; Danshi Wang; Min Zhang; Zichen Liu; Quan You; Qi Yang; Shaohua Yu (IEEE Photonics Journal, 2017)
A finer-grid wavelength-selective switch (WSS) based on liquid crystal on silicon is proposed, fabricated, and demonstrated. Based on the cost-effective method, namely combined lenses technique, the focal length is increased so that both the bandwidth setting resolution and grid granularity is improved from 12.5 to 6.25 GHz compared with the conventional WSS. To demonstrate its utility, we apply this finer-grid WSS to a reconfigurable optical add/drop multiplexer structure and an all-optical wavelength conversion (AOWC) module. To enable a finer-grid WSS, the performance of a finer-grid elastic optical network (EON) capable of AOWC is also investigated. Different from the conventional AOWC scheme for fixed-grid WDM networks, we propose and experimentally demonstrate a four-wave-mixing-based AOWC module specifically for EON. In addition to physical experiments, an optical network's control and management scheme corresponding to the designed physical scenario is also investigated. Experimental and simulation results show that the proposed method achieves higher spectrum efficiency, lower blocking probability, finer switching granularity, and higher conversion resolution.